2022
DOI: 10.18393/ejss.1135515
|View full text |Cite
|
Sign up to set email alerts
|

Biomass yield, soil cover and minerals accumulation by two green manures species grown in soils of Chiapas Mexico

Abstract: The aim of the current study was to assess the performance of Canavalia ensiformis and Mucuna deeringiana (Leguminosae) as a green manure in the agricultural soil of the Frailesca region of Chiapas, México, in terms of aboveground biomass accumulation, plant height, number of leaves, canopy coverage, and the accumulation of nitrogen (N), phosphorus (P), and potassium (K). Each species was sowed at two population densities under a randomized complete block design with three replications. Every 30 days after sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Our results revealed that, in general, aboveground DM progressively increased in all six varieties with increasing maturity, which is considered a natural phenomenon in favorable conditions new tissues and organ are formed with the progression of maturation. A similar trend has already been reported in other species of legumes with potential as green manures and forage (Matos et al, 2008;Odhiambo, 2010;Perdigão et al, 2012;Prusiński, 2014;Solati et al, 2017;Dhamala et al, 2017;Zapata et al, 2019;Hernández et al, 2022). On the other hand, the aboveground biomass yields measured in this study were in the range of those reported by other authors, who reported values up to 8000-10 000 Kg ha -1 of DM in different legumes under favorable conditions (Dubrovskis et al, 2011;Talgre et al, 2012;Dhamala et al, 2017).…”
Section: Above-ground Biomass Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results revealed that, in general, aboveground DM progressively increased in all six varieties with increasing maturity, which is considered a natural phenomenon in favorable conditions new tissues and organ are formed with the progression of maturation. A similar trend has already been reported in other species of legumes with potential as green manures and forage (Matos et al, 2008;Odhiambo, 2010;Perdigão et al, 2012;Prusiński, 2014;Solati et al, 2017;Dhamala et al, 2017;Zapata et al, 2019;Hernández et al, 2022). On the other hand, the aboveground biomass yields measured in this study were in the range of those reported by other authors, who reported values up to 8000-10 000 Kg ha -1 of DM in different legumes under favorable conditions (Dubrovskis et al, 2011;Talgre et al, 2012;Dhamala et al, 2017).…”
Section: Above-ground Biomass Yieldsupporting
confidence: 91%
“…A decrease in N concentration with successive harvest dates was reported in other studies with different species and conditions, possibly due to the dilution effect of greater above-ground biomass. Similarly, a decreasing trend in N content has been reported for different forage crops and green manures in one season of growth as the plant matured beyond flowering (Odhiambo 2010;Dhamala et al, 2017;Zapata et al, 2019;Hernández et al, 2022). According to Müller et al (1988), the biomass production of a green manure is important when incorporating it into the soil, but it is necessary to also consider its concentration of N, as this is an important chemical characteristic that governs the rate of decomposition and mineralization into the soil.…”
Section: Above-ground Biomass Yieldmentioning
confidence: 94%